2019
DOI: 10.1101/670984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered m6A modification of specific cellular transcripts affects Flaviviridae infection

Abstract: 35The RNA modification N6-methyladenosine (m 6 A) can modulate mRNA fate and thus 36 affect many biological processes. We analyzed m 6 A modification across the transcriptome 37 following infection by dengue virus (DENV), Zika virus (ZIKV), West Nile virus (WNV), and 38 hepatitis C virus (HCV). We found that infection by these viruses in the Flaviviridae family alters 39 m 6 A modification of specific cellular transcripts, including RIOK3 and CIRBP. During viral 40 infection, the addition of m 6 A to RIOK3 pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 113 publications
7
42
1
Order By: Relevance
“…m6A RNA methylation is involved in diverse biological processes, such as differentiation and pluripotency of stem cells, embryogenesis, DNA damage response as well as the transcription, alternative splicing, nuclear export, translation and degradation of mRNAs ( Batista et al, 2014 ; Xiang et al, 2017 ; Zhao et al, 2017 ; Sun et al, 2019 ). More and more studies have shown that abnormal m6A RNA methylation plays a crucial role in the pathogenesis of many human diseases including cancers ( Liu et al, 2018 ; De Jesus et al, 2019 ; Devaux and Nossent, 2019 ; Gokhale et al, 2019 ; Liu X. et al, 2019 ). However, little is known about m6A RNA methylation in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…m6A RNA methylation is involved in diverse biological processes, such as differentiation and pluripotency of stem cells, embryogenesis, DNA damage response as well as the transcription, alternative splicing, nuclear export, translation and degradation of mRNAs ( Batista et al, 2014 ; Xiang et al, 2017 ; Zhao et al, 2017 ; Sun et al, 2019 ). More and more studies have shown that abnormal m6A RNA methylation plays a crucial role in the pathogenesis of many human diseases including cancers ( Liu et al, 2018 ; De Jesus et al, 2019 ; Devaux and Nossent, 2019 ; Gokhale et al, 2019 ; Liu X. et al, 2019 ). However, little is known about m6A RNA methylation in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In infected target cells, erasure of N6-methyladenosine (m6A), the most abundant modification of messenger (m)RNA, was shown to be profitable for particle production for several flaviviruses including hepatitis C virus (HCV) and ZIKV [190,191]. In contrast, Flaviviridae infection has recently been shown to increase the expression of specific cellular factors (such as RIOK3 and CIRBP) that turned to enhance viral infection, through the modification of the m6A levels on their corresponding mRNAs [192]. Moreover, virus-specific PTMs (such as dimethylcytosine species m5Cm and m44C) were only present in the ZIKV and HCV RNA genomes isolated from virions and enhanced viral replication though the recruitment of the nuclear DEAD-box containing RNA helicase DDX6 [193].…”
Section: Modulation Of the Neuro-epigenome By Arbovirusesmentioning
confidence: 99%
“…The remarkable diversity of PTMs that have already been identified on both cellular [192] and viral RNAs [193] suggests not only very broad functional consequences, but also the likelihood that the high degree of modification of the PTM landscape induced by RNA viruses, illustrated by the Zika-induced alteration of m6A topology in host mRNAs, may have deleterious effects on a wide range of mechanisms involved in the development and control of cognitive function.…”
Section: Modulation Of the Neuro-epigenome By Arbovirusesmentioning
confidence: 99%
“…For instance, depletion of certain m 6 A regulators in HCV can enhance viral activity, which increases virus titers without disturbing viral replication ( 79 ). Moreover, HCV infection affects host immunity in an m 6 A-dependent manner ( 80 ). m 6 A modification has also been observed in HBV, and is associated with virus reverse transcription ( 81 ).…”
Section: Relationship Between Hepatocellular Carcinoma and Viral Hepamentioning
confidence: 99%